Isbanban Foundation Volunteers during the Covid-19Pandemic: Activities & Innovation - Putra, Ariza Bima; Puspitasari, Puspitasari (UI Scholars Hub, 2021)
ISBANBAN is an educational driving foundation in Banten that arranges programs to achieve curriculum goals in schools through 21st Century Skill that elaborates and encourages the ability of fostered to master the skills of Communication, Collaboration, Critical Thinking and Creativity for children aged 4 - 12 years old. Since the Covid-19 pandemic and the adoption of large-scale social restrictions and physical distancing by the government, this affected the voluntary activities carried out at Isbanban Foundation. Therefore, the purpose of this study is to obtain information about the ISBANBAN volunteers activities in Banten during this covid-19 pandemic, as well as innovative activities created by Isbanban in the education sector. The researcher found that all activities that required interaction with the Isbanban program were terminated; The closed access to the villages and lack of internet and gadgets by Isbanban students became an obstacle to online activities during the pandemic. The program provided is mentoring and prioritizing scholarships for students whose their parents’ work was affected by covid-19. The mentoring program can also still be carried out through telephone connections which are conducted every two weeks by the mentor. Another innovation given by the Isbanban Foundation to its volunteers is Online Skill Class, which every week ISBANBAN volunteers are given online soft skill training by practitioners. Through this training, it is hoped that when the activity returns to normal, the volunteers will have better capabilities to carry out their duties.